Recentrifugation of Lithium Heparin Gel Separator Tubes up to 8 h after Blood Collection Has No Relevant Influence on the Stability of 30 Routine Biochemical Analytes. (23rd October 2019) - van Balveren, Jasmijn A; Gemen, Eugenie F A; Kusters, Ron
Abstract: Background: Venipuncture for the purpose of blood analysis is often performed at remote locations, and samples may be centrifuged locally to preserve the integrity of analytes. At the central laboratory, these tubes may be centrifuged again in the routine process. However, limited research shows that >1 centrifugation cycle of gel separator tubes causes significant changes in analytes, in particular troponin I and potassium. These preanalytical test changes are undesirable and may lead to errors in diagnosis and treatment of patients. Methods: Ten volunteers donated blood in 10 lithium heparin gel tubes. Per volunteer, 5 tubes were centrifuged with Becton Dickinson centrifugation settings and 5 tubes with our local centrifugation settings. For each centrifugation setting, 1 tube was centrifuged directly after venipuncture; the second tube, directly after venipuncture and again after 4 h; the third tube, directly after venipuncture and again after 8 h; the fourth tube, 4 h after venipuncture; the last tube, 8 h after venipuncture. Thirty routine chemistry analyses were performed in plasma directly after the last centrifugation cycle. All tubes were kept at room temperature. Analytes were considered unstable when the mean percentage deviation exceeded the total allowable error. Results: Except for calcium, which slightly exceeded the predefined total allowable error limit, all the investigated analytes remained stable up to 8 h after a second centrifugation cycle with both centrifugation settings. Conclusion: This study shows that recentrifugation up to 8 h after blood collection does not cause relevant deviations in test results and may be applied safely.